2021
DOI: 10.1021/acsestwater.1c00141
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Catalytic Ozonation of Antibiotics Using Mn and Cu Oxides on γ-Al2O3 Pellets in a Micropacked Bed Reactor

Abstract: Today, the Al2O3-supported catalyst in the heterogeneous catalytic ozonation system attracts attention due to its stable structure and relatively high surface activity. Herein, Mn and Cu oxides loaded on γ-Al2O3 pellets were prepared using an impregnation method to improve the removal efficiency in a micropacked bed reactor (μPBR). The effects of the initial pH, the ratio of O3 to chemical oxygen demand (COD), and HO• scavenger on the catalytic performance were investigated. Experimental results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The main drawback of this strategy is the implementation for the treatment of large water streams. On the other hand, advanced methodologies involving the use of supported catalysts on porous materials, such as pillared clays, active carbon (Gupta and Garg, 2019), alumina (Cao et al, 2021), SiC, and ZrO 2 , (Nieto-Sandoval et al, 2021) enhance the efficiency of the process and especially the pollutant streams treated, whereby the volume of pollutant that can be degraded is significantly higher. The principal limitation in these systems is obtaining a durable anchorage or grafting of active catalyst on the porous support, which is crucial for the catalyst stability by hindering the deactivation by catalyst leaching (Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The main drawback of this strategy is the implementation for the treatment of large water streams. On the other hand, advanced methodologies involving the use of supported catalysts on porous materials, such as pillared clays, active carbon (Gupta and Garg, 2019), alumina (Cao et al, 2021), SiC, and ZrO 2 , (Nieto-Sandoval et al, 2021) enhance the efficiency of the process and especially the pollutant streams treated, whereby the volume of pollutant that can be degraded is significantly higher. The principal limitation in these systems is obtaining a durable anchorage or grafting of active catalyst on the porous support, which is crucial for the catalyst stability by hindering the deactivation by catalyst leaching (Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…13−16 Owing to these features, μPBRs have been used in gas−liquid−solid and gas−liquid reactions, such as hydrogenations, 17−19 oxidations, 20,21 absorption of CO 2 , 22 and wastewater treatments by ozonolysis. 23,24 The reduced dimension of reactors and particles can shift the dominant force of the fluid from the gravity to capillary force, resulting in a high pressure drop and energy consumption of μPBRs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the superiority of micropacked bed reactors (μPBRs) for mass transfer enhancement has received much attention due to the small particle size ( d p < 500 μm) and reactor volume. Typical mass transfer results of μPBRs showed that gas–liquid volumetric mass transfer coefficients and external volumetric mass transfer coefficients were 0.12–0.39 and 0.15–2.76 s –1 , respectively, which were higher than those of STRs and TBRs. , Also, μPBRs have several advantages of fast heat removal, catalyst immobilization, plug flows, and improved safety. Owing to these features, μPBRs have been used in gas–liquid–solid and gas–liquid reactions, such as hydrogenations, oxidations, , absorption of CO 2 , and wastewater treatments by ozonolysis. , The reduced dimension of reactors and particles can shift the dominant force of the fluid from the gravity to capillary force, resulting in a high pressure drop and energy consumption of μPBRs.…”
Section: Introductionmentioning
confidence: 99%